Effect of Distribution Channels and Prices on Consumer Loyalty in SPBU SHELL Perbaungan: Effect of Distribution Channels and Prices on Consumer Loyalty in SPBU SHELL Perbaungan - Debby Ayu (Junal Ilmu Manajemen, 2020)
This research was conducted at the Shell Perbaungan gas station engaged in the sale of fuel to meet the needs of public vehicles. The research objective was to determine the effect of partially and simultaneously the influenced of distribution channels and prices toward consumer loyalty. This type of research used associative, with quantitative approaches. The population studied was all consumers at the Perbaungan Shell gas station so that the amount could not be determined with certainty, the sample was taken at random with the Purba formula so that the number of samples taken was 100 respondents. Sources of research data using primary data and secondary data, data collection techniques using library research, questionnaires, interviews and observations. Data analysis techniques using multiple linear regression, test classic assumptions and hypothesis testing. Based on the results of the study showed that simultaneous distribution channels and prices together have positive and significant effectedtoward consumer loyalty. Partially showed the distribution channel has no significant effectedtoward consumer loyalty, while the price has significant effectedtoward consumer loyalty at the Shell Perbaungan gas station. The coefficient of determination showed that the distribution channel and price have moderate (not strong enough) relationship to consumer loyalty. R square coefficient (R2) of 0.170 shows that consumer loyalty could be explained by the distribution channel and the price of 17% and the remaining 83% explained by other variables outside the scope of research that was not done.